Intimate partner violence among postpartum women: associated factors - Karla Oliveira Marcacine; Erika de Sá Vieira Abuchaim; Larissa Jardini; Kelly Pereira Coca; Ana Cristina Freitas de Vilhena Abrão
ABSTRACT Objective: To identify the profile and assess the self-esteem of postpartum women, to characterize their babies and partners, and to verify the association of these characteristics with the occurrence of intimate partner violence (IPV). Method: Cross-sectional study with 207 postpartum women assisted in a public clinic. Results: There was no statistic correlation among the sociodemographic variables, personal and obstetric characteristics with the occurrence of IPV. The postpartum women who showed low self-esteem presented a higher exposure risk to IPV (p<0.01; OR=2.01 and CI 95% [1.40-2.87]). The mothers of the babies that were born with low weight (less than 2,500 g) had almost twice the chances of suffering violence (p<0.05; OR=1.74 and CI 95% [1.00-3.03]). The women whose partners did not consume alcohol presented a lower probability to be exposed to IPV (p<0.05; OR=0.182 and CI 95% [0.03-0.93]). Conclusion: Women's low self-esteem, babies' inappropriate weight and consumption of alcohol by partners were correlated to the occurrence of IPV.